Pemberdayaan UMKM dan Optimalisasi Literasi Masyarakat melalui Program KKN di Kelurahan Pohjentrek - Yasmin Yasmin; Kusno Hadidjija; Eka Aprilia Ariyanto; Faizatur Rochmah; Risalatul Muarifah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The 2025 Real Work Lecture Program (KKN) of PGRI Wiranegara University (UNIWARA) Team 12 was carried out in Pohjentrek Village with a focus on empowering MSMEs, improving literacy, environmental education, food security, and character education. The main issues identified include low awareness among SME actors regarding the importance of business legality, low basic literacy skills among elementary school students, high rates of open waste burning, and the emergence of social issues related to bullying among teenagers. The methods used include mentoring, socialization, training, and active participation in community activities. The results of the activities showed that 15 MSMEs were successfully registered through OSS, with three of them obtaining NIB and halal certificates; tutoring and regular literacy assistance twice a week improved students' literacy skills; the initiation of a community literacy corner began to be implemented in one of the neighborhood associations (RT); socialization of waste management encouraged four households to practice composting; the introduction of vertical farming through the distribution of vegetable seeds supported family greening and food security; and anti-bullying socialization at SMPN 6 helped students recognize their potential using the SMART method. The conclusion of this program is that KKN is able to provide a multidimensional impact through collaboration between students, the community, and the village government, while strengthening community awareness of business legality, literacy, the environment, food, and character.